2018
DOI: 10.35530/it.069.01.1440
|View full text |Cite
|
Sign up to set email alerts
|

Comfort properties of nano-filament polyester fabrics: sensory evaluation

Abstract: Proprietățile de confort ale țesăturilor din nano-filament de poliester: evaluare senzorială În acest articol, este prezentată o lucrare experimentală pentru evaluarea proprietăților senzoriale ale țesăturilor din nano-filament de poliester. În acest scop, o țesătură din nano-filament de poliester a fost realizată și comparată cu țesături din: amestec poliester/bumbac (PC) şi, respectiv, poliester/viscoză (PV), utilizând sistemul de evaluare Kawabata (sistemul KES), cu scopul de a evalua tușeul pe baza caracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…E-glass in blend with Polyester or Nylon composite yarns doesn't have many applications in this area. Such combinations have not been studied before and now this research gap will be filled through this study by combining high performance properties of glass fiber along with some normal filaments like polyester and nylon for cost benefits and flexural properties in final product [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-glass in blend with Polyester or Nylon composite yarns doesn't have many applications in this area. Such combinations have not been studied before and now this research gap will be filled through this study by combining high performance properties of glass fiber along with some normal filaments like polyester and nylon for cost benefits and flexural properties in final product [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Jeffery W. Simons, Hyung-Seop Shin, Donald A. Shockey, and David C. Erlich elaborates the cut resistance of some yarns manufactured form high performance fibers like Spectra, Kevlar and Zylon [17]. This was done under shear-tension loading mechanism by penetrating a blade like knife in transverse direction of yarns at a constant rate while each yarn was firmly held from both ends in jaws [10]. It was found that the strain to initiate a cut and total energy required to cut are highly affected by the blade sharpness, yarn tension between both jaws and finally the slicing angle.…”
Section: Introductionmentioning
confidence: 99%